Adverse childhood experiences in New Zealand and subsequent victimization in adulthood: Findings from a population-based study. (July 2021) - Fanslow, Janet; Hashemi, Ladan; Gulliver, Pauline; McIntosh, Tracey
Abstract: Background: Adverse childhood experiences (ACEs) are widespread and are associated with adverse outcomes in later life, yet few studies have explored their prevalence and consequences in New Zealand. Objectives: To provide prevalence estimates of ACEs in New Zealand using a large sample of adults, and to explore the associations between ACEs and experience of violence by intimate partners and non-partners in adulthood. Participants and setting: 2, 887 participants (1464 female, 1423 male) from the 2019 New Zealand Family Violence Survey, a population based study conducted in New Zealand between March 2017–March 2019. Methods: Descriptive statistics for prevalence of each of the eight ACE types, and cumulative ACE scores were estimated across sociodemographic groups. Multivariate logistic regression models were developed to assess association between ACEs and five IPV and two non-partner violence variables. Results: ACEs were prevalent and co-occurring, with 55 % (95 % CI 53.2 %–56.8 %) of respondents reporting having experienced at least one ACE and 11.6 % (95 % CI 10.4 %–12.8 %) reporting at least four ACEs before the age of 18. Those who were younger, had lower socioeconomic status, and who identified as Māori reported higher prevalence of ACEs. Exposure to any ACE was significantly associated with later exposure to IPV and non-partner violence. Conclusions: The findings provide the first comprehensive assessment of the prevalence of ACEs in the New Zealand population. They suggest that prevention of childhood trauma, maltreatment, and family dysfunction remain important and interconnected public health goals that need to be addressed to support the wellbeing of children and adults.